Pengaruh model pembelajaran team games tournament berbantuan media papan diagram (PADI) terhadap kemampuan pemecahan masalah siswa kelas V - Khaerunisah, Eka Endang; Zulmi Roestika Rini (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2024)
This purpose of this research was to know the effect of the TGT cooperative learning model assisted by board diagram media on the problem solving abilities of fifth grade students in data presentation material. This study used a quantitative method of experimental type with nonequivalent control group design. The population in this study were fifth grade students at SDN Gedanganak 02 and SDN Gedanganak 03. In collecting data, this research used test techniques, questionnaires and documentation. Data analysis techniques used the normality test, homogeneity test, independent sample t-test, simple linear regression test. The results showed that there was an influence of the TGT learning model using board diagram media on students' problem solving abilities as evidenced by tcount = 5,805 > ttable = 2,110 and a significance value of 0.000 <0.05 and influencing the problem solving ability variable by 49.8%. So it can be concluded that the team games tournament (TGT) learning model using board diagram media can affect students' problem solving abilities. Keywords: Team Games Tournament; Diagram Board; Problem Solvinghis purpose of this research was to know the effect of the TGT cooperative learning model assisted by board diagram media on the problem solving abilities of fifth grade students in data presentation material. This study used a quantitative method of experimental type with nonequivalent control group design. The population in this study were fifth grade students at SDN Gedanganak 02 and SDN Gedanganak 03. In collecting data, this research used test techniques, questionnaires and documentation. Data analysis techniques used the normality test, homogeneity test, independent sample t-test, simple linear regression test. The results showed that there was an influence of the TGT learning model using board diagram media on students' problem solving abilities as evidenced by tcount = 5,805 > ttable = 2,110 and a significance value of 0.000 <0.05 and influencing the problem solving ability variable by 49.8%. So it can be concluded that the team games tournament (TGT) learning model using board diagram media can affect students' problem solving abilities.Keywords: Team Games Tournament; Diagram Board; Problem Solving